Prevalence of being ‘high-risk’ of hospitalization due to exacerbation among asthma patients aged ≥ 20 years in a district of Sri Lanka. - Dhanusha Punyadasa; Vindya Kumarapeli; Wijith Senaratne (College of Community Physicians of Sri Lanka, 2024)
Introduction: Hospitalizations due to exacerbated asthma remai ns high in Sri Lanka leaving a huge burden on the healthcare system. Identification of the burden of 'high risk asthma  patients' for hospitalization due to exacerbation is a cost-effective strategy for prioritizing management options. Objectives: To estimate the prevalence of 'high-risk asthma patients ' and selected risk predictors for hospitalization due to exacerbation among asthma patients aged ≥20 years in the district of  Gampaha, Sri Lanka Methods: A community-based descriptive cross-sectional study was  conducted among 1200 asthma patients aged ≥20 years, selected using a multistage sampling technique. The risk for hospi talization was assessed using a newly developed and validated risk prediction model. High-risk asthma patients were defi ned according to the cut-off value of the summary risk score of the model. Results: The prevalence of 'high-risk asthma patients' for hospitali zation due to exacerbation was 16.4% (95% CI: 14.2, 18.6). The prevalence of selected risk predictors: age ≥ 60 years 24.2%  (95% CI: 21.9, 26.7), poor educational attainment 67.3% (95% CI: 64.5, 70.0), having diabetes mellitus 18.8% (95%  CI: 16.5, 21.0), family history of asthma 41.3% (95% CI: 38.5, 44.2), ever smoked 12.2% (95% CI: 10.2, 14.1), ever int ubated or given intensive care 2.8% (95% CI: 1.8, 3.7), previous hospitalizations due to exacerbations 6.6% (95% CI: 5.1, 8.0) , having uncontrolled asthma 63.6% (95% CI: 60.8, 66.7), having symptomatic GORD 18% (95% CI: 15.7, 20.2) and ha ving body mass index (BMI) ≥ 25 kg/m2 36.3% (95% CI: 33.5, 39.0). Conclusions & Recommendations: A significant proportion of asthm a patients being at risk of hospitalization indicates the need to adopt cost-effective asthma management strategies to ac hieve better control of the disease. Prompt primary healthcare interventions are required to address modifiable risk predi ctors among asthma patients.